Metal-doped carbon nanodots for enhanced oil recovery and applications thereof

CN117801799BActive Publication Date: 2026-11-03PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211169366.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-23
Publication Date
2026-11-03
Estimated Expiration
2042-09-23

AI Technical Summary

Technical Problem

Existing technologies are costly and have poor adaptability in improving the oil recovery rate of low-permeability, low-porosity, and tight lithological reservoirs, and their wettability improvement performance is limited, making it difficult to effectively improve the recovery rate.

Method used

Using metal-doped carbon nanodots as an oil displacement agent, the oil recovery rate is improved by changing the wettability of the rock surface through adsorption, reducing the adhesion of crude oil, and utilizing the displacement effect. It is suitable for steam injection development and water drive processes in heavy oil and light oil reservoirs.

Benefits of technology

It significantly improves crude oil recovery, reduces costs, enhances the interfacial bond between rock and crude oil, improves heat utilization and water utilization, reduces lifting energy consumption, and the material is environmentally friendly, non-toxic, and simple to prepare.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117801799B_ABST
    Figure CN117801799B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of improving oil recovery, and particularly relates to carbon nanodots for improving oil recovery, a preparation method and application thereof. The carbon nanodots are metal-doped carbon nanomaterials. Raw materials of the carbon nanodots include the following components: a carbon source, a nitrogen source, a metal source and a solvent. When the object of use is a thin oil reservoir, the carbon nanodots are mixed with oil displacement agents, etc., and after uniform mixing, they are injected into injection wells together to carry out on-site oil displacement work; when the object of use is a thick oil reservoir, the carbon nanodot raw materials are first injected into the reservoir from the injection well, and then high-temperature steam is injected to generate carbon nanodots on site under the conditions of high temperature and high pressure in the reservoir. The generated carbon nanodots are adsorbed in the rock nanometer pores to strip out the crude oil, thereby achieving the purpose of improving oil recovery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of enhanced oil recovery technology, specifically relating to a metal-doped carbon nanodot for enhancing oil recovery and its application. Background Technology

[0002] More than 80% of oil and gas resources are characterized by low permeability, low porosity, tight lithology, low quality, ultra-deep formations, and high risk. Most of the developed areas are in the middle and late stages of development, facing challenges such as high water cut, deterioration of reservoir properties, low efficiency, and high investment. They are generally entering the secondary and tertiary oil recovery stages, and the difficulty of extraction is increasing day by day.

[0003] Waterflooding technology is the main method for secondary oil recovery in oil and gas fields. It is low-cost, but production wells suffer from severe conical drilling and high water cut. Currently, the water cut of most oil reservoirs in China is over 80%, resulting in serious ineffective water injection. In deep oil reservoirs, water injection for lifting consumes a lot of energy. In the process of steam injection development of heavy oil, the steam sweep efficiency decreases with the increase of the number of injection cycles, affecting production. In order to address the above series of problems, it is urgent to develop a low-cost and high-efficiency oil recovery system to improve crude oil recovery.

[0004] Existing technologies provide methods for enhancing oil recovery using nanosystems. Chinese invention patent application CN201810838339.7 provides a bio-based nanofluid and its application in enhancing oil recovery in low-permeability reservoirs; Chinese invention patent application CN202010797780.2 provides a modified nano-graphene oxide as a chemical agent for enhancing oil recovery in low-permeability reservoirs; Chinese invention patent application CN201810187806.4 provides a surface-modified nano-silica nanofluid for enhancing oil recovery, which can reduce the interfacial tension between oil and water. However, all of these technologies are costly, require stringent preparation conditions, have poor reservoir adaptability, and offer limited improvement in wettability. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides carbon nanoparticles for improving oil recovery. These nanoparticles are easily adsorbed onto rock surfaces, thereby altering the wettability of the rock surface, reducing the adhesion of crude oil, making it easier to peel off, and further utilizing displacement to improve oil recovery.

[0006] To achieve the objectives of this invention, the following technical solution is adopted:

[0007] A carbon nanodot for improving oil recovery, wherein the carbon nanodot is a metal-doped carbon nanomaterial.

[0008] Preferably, the metal is at least one selected from Zn, Cu, Mn, and Ca, and more preferably Zn, Mn, and Ca; Zn is the most preferred.

[0009] Preferably, the metal accounts for 0.5-10 wt% of the mass of the carbon nanodots.

[0010] Preferably, the raw materials for the carbon nanodots include the following components: carbon source, nitrogen source, metal source, and solvent.

[0011] Preferably, the metal source is one or more of citrate, zinc chloride, manganese chloride, manganese sulfate, copper sulfate, calcium chloride, and zinc sulfate.

[0012] Preferably, the carbon source is one or more of citric acid, citrate, oxalic acid, oxalate, acetic acid, acetate, and tartaric acid and tartarate.

[0013] Preferably, the nitrogen source is one or more of ethylenediamine and urea.

[0014] Preferably, the solvent is one or more selected from water, ethanol, toluene, formic acid, xylene, tetrahydrofuran, and methanol. Another object of the present invention is to provide a method for preparing the above-mentioned carbon nanodots, comprising mixing a carbon source, a metal source, a nitrogen source, and a solvent, reacting at 100-300°C to obtain a liquid product.

[0015] Preferably, the molar concentrations of the carbon source, metal source, and nitrogen source in the liquid product are 0.1-0.5M, 0.1-0.5M, and 0.1-2M, respectively.

[0016] Preferably, the reaction time is 6 hours or more.

[0017] Preferably, if metal-doped carbon nanodots are to be prepared for later use, the liquid product can be further prepared into a lyophilized powder, specifically by freezing the liquid product at -50°C and then lyophilizing it under vacuum.

[0018] Another object of the present invention is to provide the application of carbon nanodots in oil displacement.

[0019] Preferably, the application includes use as a nano-displacement agent for heavy oil reservoirs developed by steam injection or as a nano-displacement agent for light oil reservoirs.

[0020] Preferably, the method of using the nano-displacement agent in the development of heavy oil reservoirs by steam injection is as follows: after mixing carbon source, metal source and nitrogen source with solvent, the mixture is injected into the reservoir in liquid form, and then steam at 150-250°C is injected from the wellhead of the injection well to generate carbon nanoparticles in situ in the reservoir for use as a displacement agent.

[0021] Preferably, the mass of the carbon nanodots accounts for 0.005-0.2% of the total injected steam.

[0022] Preferably, when the application is used as a nano-displacement agent for light oil reservoirs, the method of use is as follows: add the carbon nanoparticles to the displacement liquid, mix and use as an oil displacement agent.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0024] (1) The method for preparing the metal-doped carbon nanoparticle material of the present invention is simple and low in cost. At the same time, the material has good temperature resistance and can maintain good interfacial characteristics with oil and water. In addition, it has a smaller particle size, higher specific surface area and surface energy, and is easier to adsorb onto the rock surface without causing damage to production or formation. This changes the wettability of the rock surface, reduces the adhesion work of crude oil, and makes crude oil easier to peel off, thereby further improving the oil recovery rate by utilizing displacement.

[0025] (2) The method provided by the present invention adds metal-doped carbon nanomaterials as oil displacement agents to the water-drive oil displacement system. The added carbon nanomaterials are uniformly distributed in the oil displacement system, which can enhance the interfacial tension between the rock and the crude oil, so that the rock pores are better connected, and the crude oil in the rock pores is replaced and sealed in the nanopores. This helps to effectively change the wetting performance during the water drive process, occupy the pore space, and displace the crude oil. At the same time, the addition of the metal-doped carbon nanomaterials also improves the utilization rate of injected water, increases the amount of crude oil produced, and reduces the lifting energy consumption.

[0026] (3) The metal-doped carbon nanodots used in this invention are carbon-based conductive materials. They are hydrophilic, easily soluble in water and some organic matter, and are environmentally friendly substances. They have no toxic side effects on organisms in nature. Furthermore, the carbon nanomaterials are simple to prepare, easy to use, low in cost, and have obvious application effects. In the specific embodiments of this invention, the mid-to-late stage of waterflooding is used as the test reservoir. Metal-doped carbon nanodots are used as promoters in the oil displacement agent system. The experimental results show that they can change the synergistic effect between crude oil and rocks, so that the oil production efficiency and total oil production are significantly increased.

[0027] (4) The method provided by the present invention generates carbon nanodots in situ in the development of steam-injected heavy oil reservoirs, which greatly reduces the cost of indoor preparation. The operation process is simple and the effect is significant. It can enhance the interfacial tension between rocks and crude oil, so that the rock pores are better connected, and the heavy oil in the rock pores is replaced and sealed in the nanopores, thereby improving the thermal efficiency and thermal utilization rate and increasing the crude oil recovery rate. Attached Figure Description

[0028] Figure 1 This is a dimensional diagram of the carbon nanodots in Example 5 of the present invention;

[0029] Figure 2 This is a schematic diagram showing the time required to reach 90% of the total crude oil volume in the control group, Example 5, and Example 6 of this invention.

[0030] Experiment 1 is Example 5, and Experiment 2 is Example 6. Detailed Implementation

[0031] The present invention will be further described below with reference to specific embodiments.

[0032] Example 1

[0033] This embodiment provides a method for in-situ generation of carbon nanodots (metal-doped carbon nanomaterials) used in this invention and their application as an oil displacement agent, comprising the following steps:

[0034] Zinc citrate and urea were mixed with water to prepare a 0.5M / 0.5M mixed solution. One ton of this solution was injected into the reservoir from the wellhead. After complete injection, 10 tons of water were injected as a separator plug into the deeper formation. Then, 500 tons of high-temperature steam at 250℃ was injected from the wellhead at a pressure of 7MPa. Under the high pressure and high temperature of the formation, metal-doped carbon nanoparticles were generated in situ, which were better adsorbed on the rock surface, occupied the nanopores, and further transferred electron effects, stripping out crude oil and improving the oil recovery rate. Experimental results: The total oil production increased by 35.5% compared with the control group (using 500 tons of high-temperature steam at 250℃).

[0035] Example 2

[0036] This embodiment provides a method for in-situ generation of carbon nanodots (metal-doped carbon nanomaterials) used in this invention and their application as an oil displacement agent, comprising the following steps:

[0037] Zinc citrate and urea were mixed with water to prepare a 0.25M and 2M molar concentration mixture. One ton of this mixture was injected into the reservoir from the wellhead. After complete injection, 10 tons of water were injected as a separator plug into the deeper formation. Then, 500 tons of high-temperature steam at 220°C was injected from the wellhead. Upon reaching the formation, due to wellbore head loss, the reservoir temperature reached 200°C. Under the high pressure and high temperature of the formation, metal-doped carbon nanoparticles were generated in situ. These nanoparticles were better adsorbed onto the rock surface, occupying nanopores and further transferring electrons, thus stripping away crude oil and improving oil recovery. Experimental results: Daily oil production increased by 32.1% compared to the control group (500 tons, 250°C high-temperature steam flooding).

[0038] Example 3

[0039] This embodiment provides a method for in-situ generation of carbon nanodots (metal-doped carbon nanomaterials) used in this invention and their application as an oil displacement agent, comprising the following steps:

[0040] Oxalic acid, urea, and manganese carbonate were mixed with water to prepare mixed solutions with molar concentrations of 0.1M, 1M, and 0.2M, respectively. One ton of this mixed solution was injected into the reservoir from the wellhead. After complete injection, 10 tons of water were injected as a separator plug into the deeper formation. Then, 500 tons of high-temperature steam at 250°C was injected from the wellhead at a pressure of 7 MPa. Under the high pressure and high temperature of the formation, metal-doped carbon nanoparticles were generated in situ, which were better adsorbed on the rock surface, occupied nanopores, and further transferred electron effects, stripping crude oil and improving oil recovery. The total oil production increased by 29.7% compared to the control group (500 tons of high-temperature steam at 250°C).

[0041] Example 4

[0042] This embodiment provides a method for in-situ generation of carbon nanodots (metal-doped carbon nanomaterials) used in this invention and their application as an oil displacement agent, comprising the following steps:

[0043] Calcium citrate and urea were mixed with water to prepare a 0.5M / 0.5M mixed solution. One ton of this solution was injected into the reservoir from the wellhead. After complete injection, 10 tons of water were injected as a separator plug into the deeper formation. Then, 500 tons of high-temperature steam at 250℃ was injected from the wellhead at a pressure of 7MPa. Under the high pressure and high temperature of the formation, metal-doped carbon nanoparticles were generated in situ, which were better adsorbed on the rock surface, occupied the nanopores, and further transferred electron effects, stripping out crude oil and improving the oil recovery rate. Experimental results: The total oil production increased by 30.4% compared with the control group (500 tons of high-temperature steam at 250℃).

[0044] Example 5

[0045] This embodiment provides a method for preparing carbon nanodots (metal-doped carbon nanomaterials) used in this invention, which includes the following steps:

[0046] (1) Zinc citrate and urea are mixed with water to prepare a mixed solution with molar concentrations of 0.25M and 2M. The mixed solution is poured into a reaction vessel, and oil displacement agent is added to the solution with water to make up to 500mL. The solution is kept in a forced-air drying oven at 200℃ for 6h.

[0047] (2) Then the reaction vessel was cooled to room temperature, the liquid sample was taken out and placed in a freeze dryer, and its temperature was kept at -50°C. After the liquid sample was completely frozen into ice solid, the vacuum pump was turned on and the vacuum was drawn until the liquid was completely removed, thus obtaining the carbon nanomaterial (zinc doped).

[0048] In a specific embodiment of the present invention, the instruments used in the oil displacement system are all laboratory water-driven oil displacement test systems. The carbon nanomaterial (zinc doped) of Example 5 is added to water to prepare an oil displacement mixed solution with a displacement volume of 500 mL. The concentration of the metal-doped carbon nanomaterial of Example 5 is 3%, and the control group is pure tap water for oil displacement.

[0049] After the system has been running stably for a week, the crude oil recovery efficiency is calculated based on the amount of oil produced at the production end. According to the calculation, the recovery rate of the experimental group with a metal-doped carbon nanomaterial concentration of 3% in Example 1 is 91.6%, which is 33.8% higher than the recovery rate of 57.8% of the control group with pure water.

[0050] Example 6

[0051] This embodiment provides a method for preparing carbon nanodots (metal-doped carbon nanomaterials) used in this invention, which includes the following steps:

[0052] (1) Zinc citrate and urea are mixed with water to prepare a mixed solution with molar concentrations of 0.25M and 2M. The mixed solution is poured into a reaction vessel and kept in a drying oven at 200℃ for 12 hours.

[0053] (2) After cooling the reactor to room temperature, take out the liquid sample and put it into the freeze dryer, keep its temperature at -50℃, and after the liquid sample is completely frozen into ice solid, turn on the vacuum pump and draw a vacuum until the liquid is completely removed to obtain carbon nanomaterials (zinc doped).

[0054] In a specific embodiment of the present invention, the instruments used in the oil displacement system are all laboratory water-driven oil displacement testing systems. The carbon nanomaterials (zinc-doped) from Example 6 were mixed with water to prepare an oil displacement solution with a volume of 500 mL. The concentration of the metal-doped carbon nanomaterials from Example 6 was 1%. This solution was then continuously injected at room temperature for 7 days. The control group used pure tap water for oil displacement.

[0055] After the system has been running stably for a week, the crude oil recovery efficiency is calculated based on the amount of oil produced at the production end. According to the calculation, the recovery rate of Experiment 2 with a metal-doped carbon nanomaterial concentration of 1% in Example 6 is 78.4%, which is 20.6% higher than the recovery rate of 57.8% of the control group with pure water.

[0056] The reason for this may be that the concentration of carbon nanodots in Example 6 is low, so they can only be adsorbed on the rock surface and cannot separate a large amount of crude oil from the rock surface, thus affecting the production of crude oil. In contrast, the concentration of metal-doped carbon nanodots in Experiment 1 of Example 5 is 3%, which can not only be adsorbed on the rock surface, but also make the rocks better aggregate through the metal-doped carbon nanomaterials, improve the electron transfer between rocks, and thus improve the oil production efficiency and total oil production.

[0057] Therefore, within the experimentally verified concentration range, when the concentration of the metal-doped carbon nanomaterials in the oil displacement system is 3%, it can significantly improve crude oil yield and total oil production, resulting in significant economic benefits.

[0058] Example 7

[0059] This embodiment provides a method for preparing carbon nanodots (metal-doped carbon nanomaterials) used in this invention, which includes the following steps:

[0060] (1) Mix calcium citrate and ethylenediamine with water to prepare a mixed solution with molar concentrations of 0.1M and 1M. Pour the mixed solution into a reaction vessel and keep it in a drying oven at 185℃ for 6 hours.

[0061] (2) Then the reaction vessel was cooled to room temperature, the liquid sample was taken out and placed in a freeze dryer, and its temperature was kept at -50°C. After the liquid sample was completely frozen into ice solid, the vacuum pump was turned on and the vacuum was drawn until the water was completely removed, and the carbon nanomaterial (metal calcium doped) was obtained.

[0062] In the specific embodiments of the present invention, the instruments used in the oil displacement system are all laboratory water-driven oil displacement test systems. In Example 7, the oil displacement volume is 500 mL, and the concentration of metal-doped carbon nanomaterials is 3%. The solvent water for the oil displacement agent comes from tap water. Subsequently, it is continuously injected at room temperature for 7 days.

[0063] Experimental results: The total oil production increased by 26.1% compared to the control group (pure tap water oil displacement).

[0064] The recovery rate in Example 7 was 83.9%, compared to 57.8% in the control group.

[0065] Example 8

[0066] This embodiment provides a method for preparing carbon nanodots (metal-doped carbon nanomaterials) used in this invention, which includes the following steps:

[0067] (1) Mix oxalic acid solution, urea and manganese carbonate with water to prepare a mixed solution with molar concentrations of 0.25M, 0.2M and 0.2M. Pour 1 ton of the mixed solution into a reaction vessel and keep it in a forced-air drying oven at 190℃ for 6 hours.

[0068] (2) Then the reaction vessel was cooled to room temperature, the liquid sample was taken out and placed in a freeze dryer, and its temperature was kept at -50°C. After the liquid sample was completely frozen into ice solid, the vacuum pump was turned on and the vacuum was drawn until the water was completely removed, and the carbon nanomaterial (zinc doped) was obtained.

[0069] In a specific embodiment of the present invention, the instruments used in the oil displacement system are all laboratory water-driven oil displacement testing systems. The oil displacement volume used in the example is 500 mL, and the concentration of metal-doped carbon nanomaterials is 3%. The solvent water for the oil displacement agent is tap water. Subsequently, it is continuously injected at room temperature for 7 days.

[0070] Experimental results: The total oil production increased by 24.6% compared to the control group (pure tap water oil displacement).

[0071] The recovery rate in Example 8 was 82.4%, compared to 57.8% in the control group.

[0072] Example 9

[0073] This embodiment provides a method for preparing carbon nanodots (metal-doped carbon nanomaterials) used in this invention, which includes the following steps:

[0074] (1) Tartaric acid, urea and calcium chloride are mixed with water to prepare a mixed solution with molar concentrations of 0.25M, 0.5M and 0.2M. 1 ton of the mixed solution is poured into a reaction vessel and kept in a forced-air drying oven at 180℃ for 6 hours.

[0075] (2) Then the reaction vessel was cooled to room temperature, the liquid sample was taken out and placed in a freeze dryer, and its temperature was kept at -50°C. After the liquid sample was completely frozen into ice solid, the vacuum pump was turned on and the vacuum was drawn until the water was completely removed, and the carbon nanomaterial (zinc doped) was obtained.

[0076] In a specific embodiment of the present invention, the instruments used in the oil displacement system are all laboratory water-driven oil displacement testing systems. The oil displacement volume used in the example is 500 mL, and the concentration of metal-doped carbon nanomaterials is 3%. The solvent water for the oil displacement agent is tap water. Subsequently, it is continuously injected at room temperature for 7 days.

[0077] Experimental results: The total oil production increased by 27.4% compared to the control group (pure tap water oil displacement).

[0078] The recovery rate in Example 9 was 85.2%, compared to 57.8% in the control group.

[0079] Comparative Example 1

[0080] The difference between this embodiment and Example 1 is that the metal source is copper citrate, while the rest is the same as Example 1. Using the method of Example 1 for oil displacement, the experimental results showed that the total oil production increased by 25.2% compared to the control group (500 tons, 250℃ high-temperature steam displacement).

[0081] Comparative Example 2

[0082] The difference between this comparative example and Example 1 is that the metal source is magnesium citrate, while the rest is the same as Example 1. Oil displacement was performed using the method described in Example 1. The experimental results showed that the total oil production increased by 15.8% compared to the control group (500 tons, 250°C high-temperature steam displacement). The control group was 500 tons, 250°C high-temperature steam displacement.

[0083] Comparative Example 3

[0084] The difference between this comparative example and Example 1 is that the metal source is silver citrate, while the rest is the same as Example 1. Oil displacement was performed using the method described in Example 1. The experimental results showed that the total oil production increased by 12.9% compared to the control group (500 tons, 250°C high-temperature steam displacement). The control group was 500 tons, 250°C high-temperature steam displacement.

[0085] Comparative Example 4

[0086] The difference between this comparative example and Example 1 lies in the concentration of the metal source, as detailed below:

[0087] Zinc citrate and urea were mixed with water to prepare a mixed solution with molar concentrations of 0.01M and 0.5M. One ton of this mixed solution was injected into the reservoir from the wellhead. After complete injection, 10 tons of water were injected as a separator plug into the deeper formation. Then, 500 tons of high-temperature steam at 250℃ was injected from the wellhead at a pressure of 7MPa. Under the high pressure and high temperature of the formation, metal-doped carbon nanoparticles were generated in situ, which were better adsorbed on the rock surface, occupied the nanopores, and further transferred electron effects, stripping out crude oil and improving the oil recovery rate. Experimental results: The daily oil production increased by 16.5% compared with the control group (500 tons of high-temperature steam at 250℃).

[0088] Comparative Example 5

[0089] The difference between this comparative example and Example 1 lies in the concentration of the metal source. Specifically,

[0090] 1.0 ton of zinc citrate aqueous solution (0.67M) and urea (0.50M) were uniformly mixed and injected into the reservoir from the wellhead. After complete injection, 10 tons of water were injected as a separator plug into the deeper formation. Then, 500 tons of high-temperature steam at 250℃ was injected from the wellhead at a pressure of 7MPa. Under the high pressure and high temperature of the formation, metal-doped carbon nanoparticles were generated in situ, which were better adsorbed on the rock surface, occupied the nanopores, and further transferred electron effects, stripping out crude oil and improving the oil recovery rate. Experimental results: The daily oil production increased by 32.8% compared with the control group (500 tons, 250℃ high-temperature steam flooding).

[0091] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.

Claims

1. A carbon nanoparticle for enhancing oil recovery, characterized in that, The carbon nanodots are carbon nanomaterials doped with metal; The raw material for the carbon nanodots consists of the following components: zinc citrate or calcium citrate, urea, and water; The method for preparing carbon nanodots includes the following steps: Zinc citrate or calcium citrate, urea and water are mixed and reacted at 100-300℃ to obtain a liquid product, which is the product; The molar concentrations of zinc citrate or calcium citrate and urea in the liquid product are 0.5M and 0.5M, respectively.

2. A method for preparing carbon nanodots as described in claim 1, characterized in that, Includes the following steps: Zinc citrate or calcium citrate, urea and water are mixed and reacted at 100-300℃ to obtain a liquid product, which is the product; The molar concentrations of zinc citrate or calcium citrate and urea in the liquid product are 0.5M and 0.5M, respectively.

3. The method for preparing carbon nanodots according to claim 2, characterized in that, The reaction time is more than 6 hours.

4. The method for preparing carbon nanodots according to claim 2, characterized in that, The preparation method further includes freezing the liquid product at -50°C and then freeze-drying it under vacuum.

5. The application of carbon nanodots as described in claim 1 or carbon nanodots prepared by any one of claims 2-4 in oil displacement.

6. The application according to claim 5, characterized in that, The applications include use as a nano-displacement agent for heavy oil reservoirs developed by steam injection or as a nano-displacement agent for light oil reservoirs.

7. The application according to claim 5, characterized in that, The method of using the nano-displacement agent in the development of heavy oil reservoirs by steam injection is as follows: after mixing carbon source, metal source and nitrogen source with solvent, the mixture is injected into the reservoir in liquid state, and then steam at 150-250℃ is injected from the wellhead of the injection well to generate carbon nanodots in situ in the reservoir for use as a displacement agent.

8. The application according to claim 5, characterized in that, The method of using the aforementioned application as a nano-displacement agent for light oil reservoirs is as follows: add the carbon nanoparticles to the displacement liquid, mix, and then use as an oil displacement agent.

Citation Information

Patent Citations

  • Surface modification nano-silicon dioxide nano-fluid for improving oil recovery

    CN108410440A

  • Bio-based nanofluids and their application in enhancing oil recovery in low-permeability reservoirs

    CN109111905B

  • Application of modified nano-graphene oxide as an enhanced oil recovery chemical in low-permeability reservoirs

    CN111978944B

  • Preparation method of metal ion doped carbon dot solution

    CN112852417A

  • Coal-based carbon quantum dot oil displacement agent and application thereof in oil and gas exploitation

    CN113528107A